Studi Kasus PT X: Telaah atas Beberapa Permasalahan Terkait Hak dan Kewajiban Wajib Pajak - Charoline Cheisviyanny; Herlina Helmy; Sany Dwita (Universitas Andalas, 2019)
This article aims to review some problems faced by PT X related to three things: the arrangement of PKP, plea of reducing income tax 25, and the status of a tax consultant. The study was carried out from the point of view of academics after conducting a semi-structure interview with the director of PT X and the corporate tax consultant. We also analyzed documents related to these problems. The results of the study show that the company considers the arrangement of PKP is complicated, a reason for rejecting the plea of reducing income tax 25 is unreasonable, and the lack of appreciation for unofficial tax consultants. So, it is recommended for the DGT to reevaluate tax rules implementation related to these matters